Teaching genesis of old Turkic alphabet and its connection with Turkic tribe Tamgas - Sadibekov, Ðskat Ðš.; Baiymbetova, Raushan K.; Myrzakhanova, Akbota Ðš.; Yergubekova, Zh.S.; Abilova, G.; Sadykova, A.D. (Jurnal Cakrawala Pendidikan, 2023)
Old Turkic inscription with 2500-years history from the beginning of the 5-4th century A.D., it has been proven that archaeologists have come to prove that European Rune has reached the Turkic steppe. Every nation in the world has its genealogy, peculiarities and viewpoints. Each nation has its own language, customs, thinking system and value. It is common today that the Old Turkic language, which has been around for 300 years, has a great deal of social studies. The main aim of this paper is that the history of old Turkic inscriptions was formed 4-5th centuries before the European Rune inscription, and that this subject should still be studied in depth. The purpose of this study is to lay the foundation for Turkologists by training future philologists, and to open the way for a more in-depth study of our vision in the future. In recent years, the discovery of many exhibits in the territory inhabited by nomads can serve as an occasion to change the content of the prediction. This paper presents the thought that old Turkic scripts inherent to them. This idea is based on the opinions of famous scientists, based on the symbols of the Old Turkic tribes. This article focuses on scientific research from current scientists. The new data presented during the training of future philologists regarding the genesis of the ancient Turkic script will be analyzed.